The role of social entrepreneurship in alleviating economic problems in society: A literature study - Ani Darliani; Wirda Wirda (Indonesia Auditing Research Journal, 2025)
Poverty is a fundamental issue that attracts the attention of governments worldwide, including Indonesia, which still has a high poverty rate. This study aims to analyze the role of entrepreneurship as a strategy to address poverty, which is complex and multidimensional, through a comprehensive and integrated approach. The research employs a qualitative approach using a literature review from various national and international sources related to poverty, entrepreneurship, and poverty alleviation strategies. The results indicate that entrepreneurship is crucial in boosting income, enhancing economic empowerment, and generating employment opportunities. Additionally, entrepreneurship utilizes local potential to promote inclusive and ustainable development